Polaron effect on the bandgap modulation in monolayer transition metal dichalcogenides. (8th November 2017) - Xiao, Yao; Li, Zhi-Qing; Wang, Zi-Wu
Abstract: We theoretically study the bandgap modulation in monolayer transition metal dichalcogenides (TMDs) originating from the carrier-optical phonon coupling in the Fröhlich polaron model, in which both of the surface optical phonons modes induced by the polar substrate and the intrinsic longitudinal optical phonons modes have been taken into account. We find that the modulated magnitude of the bandgap is in the range of 100–500 meV by altering different polar substrates and tuning the internal distance between TMDs and polar substrate. The large tunability of the bandgap not only provides a possible explanation for the experimental measurements regarding the dielectric environmental sensitivity of the bandgap, but also holds promise for potential applications in optoelectronics and photovoltaics.